2010
DOI: 10.1021/cm101130a
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Total Scattering and Simulation Approach to Analyzing Defect Structure in Bi3YO6

Abstract: The defect structure and electrical properties of the fast oxide ion-conducting solid electrolyte δ-Bi 3 YO 6 have been studied using a combination of total neutron scattering analysis, energy minimization methods, and AC impedance spectroscopy. Conventional structural analysis using the Rietveld method reveals the oxide ions to be distributed over three crystallographic sites at room temperature, with a small change in this distribution at 800 °C. Analysis of short-range correlations using a total neutron sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 52 publications
12
55
0
Order By: Relevance
“…Isovalent substitution of Bi 3+ leads to systems with nominally the same vacancy concentration as in the parent δ-Bi 2 O 3 . However, we have shown that the true vacancy concentration in these substituted bismuth oxides is increased with respect to the parent δ-Bi 2 O 3 , through creation of Frenkel defects [9].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Isovalent substitution of Bi 3+ leads to systems with nominally the same vacancy concentration as in the parent δ-Bi 2 O 3 . However, we have shown that the true vacancy concentration in these substituted bismuth oxides is increased with respect to the parent δ-Bi 2 O 3 , through creation of Frenkel defects [9].…”
Section: Introductionmentioning
confidence: 82%
“…Structure relaxation was carried out for different vacancy ordering configurations using a single unit cell model (10 atoms), with an 8 × 8 × 8 k mesh, while the random vacancy/cation configuration was relaxed using a 2 × 2 × 2 supercell (80 atoms), with a 2 × 2 × 2 k The initial lattice parameters for Bi 3 YO 6 were obtained from the neutron scattering analysis [9] at 1073 K and the atomic starting positions were based on those in the ideal fluorite structure, i.e. Bi and Y on the 4a sites and O on ¾ of the 8c sites in the Fm-3m unit cell.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of them is Bi 3 YO 6 that occurs in the δ-phase even at room temperature [14]. The defect structure, vacancy ordering, and oxygen ion transport in the Bi 3 YO 6 δ-phase were studied using ab initio molecular dynamic, as well as total neutron scattering analysis [15][16][17]. Ionic transport in a material and its defect structure are commonly tested in Bi 3 NbO 7 -Bi 3 YO 6 systems [18,19] and in tungsten-doped Bi 3 YO 6 [20].…”
Section: Introductionmentioning
confidence: 99%